IMPELEMENTASI STRATEGI PEMASARAN MELALUI SOSIAL MEDIA MARKETING PADA UMKM FFBURGER - Joy Happy Jones; Steven Steven; Fadila Amalda; Agnes Agnes (LP2M Universitas Bina Bangsa, 2023)
This research discusses how to optimize marketing through social media for ffbuge_. Currently ffburger_ is facing fierce competition from other MSMEs selling similar products. This is caused by the owner's lack of understanding of the latest business strategy developments which makes ffburger_ have a small consumer coverage and do not yet have its own brand image. Therefore, this research is aimed at providing knowledge and education regarding good Social Media Marketing strategies for ffburger_ MSMEs and helping MSMEs in maximizing the use of social media and online platforms in building a good and attractive Brand Image and increasing promotion using social media by providing guaranteed increased engagement. The method used in this research is a qualitative descriptive analysis which is collected through an interview process with the owner, surveys through questionnaires and observations are carried out in order to get the right strategy for MSME development. The results obtained by SMEs from this study are the development of a good brand image both from the number of followers on the Ffburger_ Instagram account which has increased from. In addition, the number of engagements on the Ffburger_ Instagram account is also in the last 6 days